ANALYSIS OF STUDENT ERRORS IN SOLVING THE SYSTEM OF THREE VARIABLE LINEAR EQUATIONS (SPLTV) BASED ON THE NEWMAN STAGES IN CLASS X STUDENTS AT UPT SMA NEGERI 1 PAREPARE - Hafis; Buhaerah; Sunarti; Wahyu Hidayat (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2022)
This study aims to describe the location of errors and the causes of student errors in solving the problems of the Three Variable Linear Equation System in Contextual Problems (daily life) using the Determinant Matrix Method. This material was chosen because students often make many mistakes when solving problems. This type of research is descriptive research with a qualitative approach. The subjects of this study were six students who were taken from the results of consultations with the Mathematics teacher of UPT SMA Negeri 1 Parepare. The data collection technique is a written test with three questions. . Based on the results of the study, it was concluded that students' errors in solving the problems of the Three-variable Linear Equation System in Contextual Problems (Daily Life) used the Determinant Matrix Method, namely First, the Reading Error was 13%. This is caused because students are less thorough and in a hurry to dig up the information, so the mistakes made by these students are fatal. Second, Comprehension Error is as much as 16%. This is caused because students do not write down information about what is known and asked and the information written is not appropriate. Third, a Transformation Error of 23% is caused because students cannot identify the right operation to solve the given problem. Students write the wrong sign in the arithmetic operation of the problem. Fourth, Process Kill is 19%, this is caused because students cannot carry out the calculation operation process correctly. And Fifth, Encoding Error of as much as 29% is caused because students are wrong in writing the final answer and do not write conclusions from the questions given.